Affinity Binding of Intact Fat Cells and Their Ghosts to Immobilized Insulin - Soderman, Denis D. (1973)
Immobilized insulin, prepared by coupling insulin directly to agarose or through hydrocarbon “connecting arms,” was demonstrated to be capable of firmly binding intact adipocytes and their ghosts. Various lines of evidence indicate that the insulin receptor on the plasma membrane, in addition to the insulin coupled to the agarose, was responsible for the observed binding. This evidence includes: (a) the finding that increasing the “arm” length increased the binding capacities of insulin-Sepharose affinity chromatographic columns, (b) specific inhibition and reversal by insulin and antiserum to insulin of the binding, as compared to lesser effects by other peptide hormones, (c) the indication that only the plasma membrane sacs, not the other cellular contaminants in the crude ghosts, are capable of binding, and (d) the impairment and restoration of trypsin-sensitive membrane binding sites that are also required for insulin biosensitivity. These findings support the idea that the insulin receptor is the trypsin-sensitive site. By use of the differential buoyant densities of the various cell-bead complexes that resulted from the interaction of adipocytes with insulin-Sepharose, a new procedure was developed to demonstrate and study the binding. These complexes could also be demonstrated by interference contrast microscopy. Binding readily occurred under conditions favorable for insulin stimulation of the cells. By coupling tracer amounts of [(125)I]insulin to Sepharose or insulin-Sepharose, the effects of anti-insulin antisera, free insulin, and other peptide hormones and supplemental factors on the buoyant-density distribution of the complexes could be measured, as well as the effects of other ligands coupled to Sepharose.